REGULATORY IMPACT ASSESSMENT PENGGUNAAN PRODUK DALAM NEGERI PADA PENGADAAN BARANG/JASA - Wawan Zulmawan (UNES Law Review, 2022)
This article examines how the implementation of the Regulatory Impact Assessment in assessing the regulations issued by the Indonesian government regarding the use of domestic products in the procurement of goods / services, namely the application of these rules in the practice of government procurement of goods / services as well as in State-owned enterprises. Analysis of the Impact of Regulations on the Use of Domestic Products can show that the crucial point of the Regulation for the Use of Domestic Products is that there are no rules regarding criminal sanctions if the use of domestic products is not applied in the procurement of goods / services by government agencies or BUMN. In fact, criminal sanctions are needed to be an effort to maintain compliance from government agencies or BUMN in implementing these regulations. Without criminal sanctions it will be difficult to obtain maximum application of the rules and compliance is also difficult to achieve.